Realiti Pencapaian Budaya Cemerlang Di Sekolah Dari Perspektif Pelajar - Rusli, Md. Zain (1998)
This study focuses on factors affecting the attainment of excellent cultures from the aspect of academic performance and diciplinary problems in fully residential schools in Kedah and Perlis. Among the objectives are to identify the factors which influence the achievement of excellent culture and the relationships among the factors being investigated. This study also attempted to find out negatives factors which bar the achievement of excellent culture in a fully residential school. Four factors were investigated: student factors, peer group factors, school factors and family factors. The sample consisted of 210 form four students randomly chosen from three fully residential schools: Sekolah Menengah Sains Tuanku Syed Putra Kangar Perlis, Sekolah Menengah Sultan Abdul Halim Jitra Kedah and Sekolah Menengah Sains Pokok Sena Kedah. The questionnaire was pilot tested in Sekolah Sultan Mohamad Jiwa Sungai Petani Kedah. The findings indicated that excellent culture differed significantly between and among students based on student factors viz., peer group factors, school factors and family factors. The findings also indicated that excellent culture achievement was positively related with the four factors under study. There were two outstanding factors such as family income and family involvement in the students’ activities. Both factors did not explain the positive relationship and not representing significant predictor for overall excellent culture performance. The findings also indicate that the relationship between the factors were low.